What affects people’s use of and attitudes toward gender-inclusive language? A literature review - Lange, Elena; von Stockhausen, Lisa (Frontiers in Psychology, 2025)
This review synthesizes research on factors shaping attitudes toward and use of gender-inclusive language across linguistic, cultural, and methodological contexts. Sexist beliefs consistently predict negative attitudes and lower usage. Neither gender nor age per se are reliable predictors. Use of inclusive language has risen over time, driven by shifting norms and increased exposure. Political and social environments play a role, with progressive contexts and early equality legislation linked to greater support. Situational factors—such as conversational setting and perceived audience views—and political orientation influence language choices, with liberal individuals and institutions using inclusive forms more often. People with high and low education levels share similar attitudes, and non-academics may use inclusive language more than academics in certain settings. These results underscore the importance of addressing gender stereotypes and implementing policies and training to promote gender equality in everyday communication. Future pathways for research are discussed.